Warm-up stretching exercises and physical performance of youth soccer players - Hernandez-Martinez, Jordan; Ramirez-Campillo, Rodrigo; Vera-Assaoka, Tiago; Castillo-Cerda, María; Carter-Thuillier, Bastian; Herrera-Valenzuela, Tomás; López-Fuenzalida, Antonio; Nobari, Hadi; Valdés-Badilla, Pablo (Frontiers in Physiology, 2023)
This study aims to compare the effects of standard warm-up versus warm-up using stretching exercises on the physical performance of male youth soccer players. Eighty-five male soccer players (age: 10.3±4.3 years; body mass index: 19.8±4.3 kg/m2) were assessed for countermovement jump height (CMJ, cm), 10 m, 20 m and 30 m running sprint speed (s) and ball kicking speed (km/h) for the dominant and non-dominant leg under five (randomized) warm-up conditions. Using 72 h of recovery between conditions, the participants completed a control condition (CC) and four experimental conditions, including static stretching (SSC), dynamic stretching (DSC), ballistic stretching (BSC), and proprioceptive neuromuscular facilitation (PNFC) exercises. All warm-up conditions had a duration of ten minutes. The main results indicate that no significant differences (p >0.05) were found between warm-up conditions compared to CC in CMJ (CC= 28.1±4.9; SSC= 28.4±4.9; DSC= 30.9±4.8; BSC= 30.9±5.2; PNFC= 28.4±5.0), 10 m sprint (CC= 2.42±0.4; SSC= 2.50±0.4; DSC= 2.30±0.3; BSC= 2.27±0.3; PNFC= 2.53±0.4), 20 m sprint (CC= 5.42±0.9; SSC= 5.59±0.9; DSC= 5.37±0.9; BSC= 5.40±0.9; PNFC= 5.44±0.9), 30 m sprint (CC= 8.05±1.3; SSC= 8.27±1.3; DSC= 8.01±1.3; BSC= 8.00±1.3; PNFC= 8.12±1.3), ball kicking speed for dominant (CC= 56.2±4.9; SSC= 55.3±5.2; DSC= 56.9±5.8; BSC= 57.3±5.8; PNFC= 55.7±5.2) and non-dominant leg (CC= 52.8±3.4; SSC= 51.8±4.6; DSC= 53.5±5.4; BSC= 53.6±4.9; PNFC= 52.5±4.0). In conclusion, compared to standard warm-up, stretching-based warm-up exerts no effect on male youth soccer players jump height, sprint speed and ball kicking speed.